Evaluation of Limited Face-to-Face Learning (PTM) Policies During the Covid-19 Pandemic - Elly Fitriyani; Hanny Purnamasari; Dadan Kurniansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Abstract: Public policy is the setting of goals and suggestions as well as decisions that are marked by choices or actions that have an impact on the government's decision to or not to do something that aims to achieve goals so that it can be useful for society. One of the policies made by the government as an alternative solution to problems that arise in the world of education during the COVID-19 pandemic is to prevent learning loss. SMP Negeri 2 Telukjambe Timur Karawang is a school that has met the requirements for implementing PTM in the period September-January 2022. An evaluation of the PTM policy organized by SMP Negeri 2 Telukjambe Timur needs to be done considering the urgency of face-to-face learning for students, although now Limited PTM is being abolished because the presence of a new variant of the virus which is claimed to be more dangerous. This study uses a qualitative descriptive research design which in this study aims to elaborate policy implementation by using William N Dunn's policy evaluation which consists of six indicators, namely; effectiveness, efficiency, assessment, equity, responsiveness, and accuracy.